Discovering a model Pacific oyster for sustainable aquaculture production and sales optimisation in southern Australia - Chuku, Ernest Obeng; Rust, Steven Allen; Smith, Gregory George; Mazumder, Debashish; Trotter, Andrew James (Frontiers in Sustainable Food Systems, 2024)
The Pacific oyster is prominent in global food security and the blue economy. As an unfed aquaculture species, the oyster offers substantial potential to contribute to United Nations Sustainable Development Goals related to hunger, health, and employment. By capitalising on its biophysical attributes, the industry can enhance production efficiency and economic sustainability. This study advances critical insights into commercially important biophysical traits of the Pacific oyster across its supply chains in southern Australia (South Australia and Tasmania). Applying quantitative analysis to qualitative data using proportional odds logit modelling, reflexive thematic analysis (with theme salience), Fleiss’ Kappa analyses, and a novel Industry-Acclaimed Trait Importance (IATI) Index, we identify non-specific survival, uniform growth, and shell integrity (hard, dense, and less chalky) as primary determinants of production success. The meat quality, shell appearance, and size consistency are also of prime importance for marketability. Notably, we discover the shell, which is not eaten and often overlooked in the oyster production economy, as a critical factor impacting 78% of identified biophysical traits, revealing a potential avenue for production and sales optimisation. By delineating the characteristics of a model oyster, we provide a blueprint for selective breeding and farm management practices to enhance product quality and foster sustainable Pacific oyster aquaculture.